Intrathecal immune response and virus-specific immunoglobulin M antibodies in laboratory diagnosis of acute poliomyelitis. - Roivainen, M (1993)
The intrathecal immune response in 114 patients with clinically diagnosed acute poliomyelitis was studied by measuring poliovirus-specific immunoglobulin M (IgM) antibodies in cerebrospinal fluid (CSF) by a mu-capture immunoassay and by assessing the ratio between levels of poliovirus-neutralizing antibodies in serum and CSF. Fecal specimens were used for attempts to isolate the causative agents. Eighty-five percent of CSF specimens collected during the first 15 days of disease contained virus-specific IgM antibodies. Forty-five of 48 tested children (94%) also showed virus-specific IgM responses in their sera. Later on, the antibody levels decreased, and positive results after 30 days of onset of paralytic symptoms were rare. If the presence of poliovirus-specific IgM antibodies in the CSF was considered diagnostic, more cases were confirmed by this test than by virus isolation. A relative increase in poliovirus-neutralizing antibodies in the CSF was observed in about one-third of the cases; in all but three cases the increase was observed together with the presence of virus-specific IgM antibodies. A systemic virus-specific response can be seen and poliovirus can be isolated from a subclinically infected individual suffering from a concomitant poliomyelitis-like disease, while positive results by the two methods demonstrating an intrathecal immune response are likely to indicate a true causal relationship between infection and disease. Demonstration of poliovirus-specific IgM antibodies in the CSF thus appears to be a sensitive and specific method for laboratory confirmation of clinically diagnosed poliomyelitis.